Responsibility of a Public Notary On The Making of Sale and Purchase Agreement and Authorization To Sell Without Legal Effect - Hafiza, Nurul; Saptanti, Noor; Indriyani, Rachma (International Journal of Educational Research & Social Sciences, 2025)
The purpose of this study is to analyze and understand the legal consequences of the Deed of Binding Sale and Purchase Agreement (PPJB) and Power of Attorney to Sell which are declared null and void by law and the responsibility of the Notary in making the Deed of Binding Sale and Purchase Agreement (PPJB) and Power of Attorney to Sell which are declared null and void by law/ The type of research that will be used by the author is normative or commonly called doctrinal. The approach used by the author in this study is the conceptual approach and the case approach. In this study, the legal materials that will be used are primary and secondary legal materials. The results of the study stated that the Supreme Court Decision Number 3162 K/Pdt/2021 stated that the Deed of Binding Sale and Purchase Agreement and Power of Attorney to Sell were null and void because they did not meet the valid requirements of the agreement according to Article 1320 of the Civil Code and violated the formal procedures for authentic deeds. The legal consequences of the cancellation are the return of the parties to their original state, including the return of land rights to the legal owner and the nullity of all legal actions arising from the deeds. Notaries who are negligent in exercising their authority can be held accountable civilly, administratively and criminally.